Monty's men : the British Army and the liberation of Europe, 1944-5 - Buckley, John (John D.) (Yale University Press, 2013)
"Historian John Buckley offers a radical reappraisal of Great Britain's fighting forces during World War Two, challenging the common belief that the British Army was no match for the forces of Hitler's Germany. Following Britain's military commanders and troops across the battlefields of Europe, from D-Day to VE-Day, from the Normandy beaches to Arnhem and the Rhine, and, ultimately, to the Baltic, Buckley's provocative history demonstrates that the British Army was more than a match for the vaunted Nazi war machine. This fascinating revisionist study of the campaign to liberate Northern Europe in the war's final years features a large cast of colorful unknowns and grand historical personages alike, including Field Marshal Sir Bernard Montgomery and the prime minister, Sir Winston Churchill. By integrating detailed military history with personal accounts, it evokes the vivid reality of men at war while putting long-held misconceptions finally to rest"--